Interaction of different Chlamydiae species with bovine spermatozoa - Eckert, Thomas; Goericke-Pesch, Sandra; Heydel, Carsten; Bergmann, Martin; Kauffold, Johannes; Failing, Klaus; Wehrend, Axel; Justus Liebig University Giessen (My University, 2019)
BACKGROUND: Interaction of spermatozoa and Chlamydiae spp. might contribute to reduced fertility in cattle. To proof this hypothesis, bovine semen was incubated with viable or heat inactivated Chlamydia (C.) abortus or psittaci (Multiplicity of infection = 1) and sperm motility was monitored with a computer-assisted sperm analyzer over 24 h. Additionally, the interaction with the spermatozoa was further investigated by means of light and transmission electron microscopy (TEM).RESULTS: Only viable Chlamydiae of both species decreased sperm motility and this only after about 9 h. Taking binding rates into account, the loss of sperm motility after about 9 h could likely be a consequence of Chlamydiae attachment to the spermatozoa. About two thirds of the Chlamydiae elementary bodies were bound to the front third of the sperm, the acrosomal region. No inclusions of Chlamydiae in spermatozoa were observed in TEM after 2 h co-incubation.CONCLUSIONS: As initial motility was not affected following co-incubation of viable Chlamydiae and bovine sperm, it seems likely that sperm could serve as a carrier/vehicle for Chlamydiae facilitating cervical passage of Chlamydiae spp. in cattle. Additionally, our results suggest that spermatozoa carrying Chlamydiae may have no initial disadvantage in reaching the oviduct, but are immotile at the time of ovulation what might have an impact on fertilization capacities of the individual sperm. Consequently, high concentrations of the investigated Chlamydiae in the seminal plasma or female genital tract might play a role in reduced fertility in cattle.
Keywords: chlamydiae; cattle; semen motility; CASA (computer assisted sperm analysis); ddc:630